2018
DOI: 10.1002/acn3.679
|View full text |Cite
|
Sign up to set email alerts
|

Sensorimotor plasticity after spinal cord injury: a longitudinal and translational study

Abstract: ObjectiveThe objective was to track and compare the progression of neuroplastic changes in a large animal model and humans with spinal cord injury.MethodsA total of 37 individuals with acute traumatic spinal cord injury were followed over time (1, 3, 6, and 12 months post‐injury) with repeated neurophysiological assessments. Somatosensory and motor evoked potentials were recorded in the upper extremities above the level of injury. In a reverse‐translational approach, similar neurophysiological techniques were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 36 publications
1
20
0
Order By: Relevance
“…Since the theory of spinal cord plasticity was proposed, it has become an important direction of SCI treatment. 6 In recent decades, magnetic stimulation (MS) technology has gradually attracted wide attention from researchers and clinicians because of its safety and effectiveness. Studies have shown that transcranial magnetic stimulation (TMS) can change the excitability and accelerate regeneration of nerve cells, induce axon regeneration and lateral bud growth, enhance remodeling of the nervous system, and promote motor function recovery.…”
Section: Introductionmentioning
confidence: 99%
“…Since the theory of spinal cord plasticity was proposed, it has become an important direction of SCI treatment. 6 In recent decades, magnetic stimulation (MS) technology has gradually attracted wide attention from researchers and clinicians because of its safety and effectiveness. Studies have shown that transcranial magnetic stimulation (TMS) can change the excitability and accelerate regeneration of nerve cells, induce axon regeneration and lateral bud growth, enhance remodeling of the nervous system, and promote motor function recovery.…”
Section: Introductionmentioning
confidence: 99%
“…Spinal cord injury (SCI) is a debilitating condition that leads to loss of motor function due to the severing of axonal connections and the death of neurons at the injury site (Darian-Smith 2009, Jutzeler et al 2019. While functional loss is largely permanent in adult mammals due to an inability to repair damaged tissue, teleost fish and urodele amphibians are able to recover normal locomotor behavior even after complete spinal cord transection (Becker et al 1997, Sirbulescu & Zupanc 2010.…”
Section: Introductionmentioning
confidence: 99%
“…Functional imaging and electrophysiological studies have revealed that CoRe is a physiological phenomenon in which the time elapsed after the injury may be considered a key factor. In this regard, functional changes have been observed immediately after SCI in different animal models as rodents (Aguilar et al 2010;Yagüe et al 2011Yagüe et al , 2014Humanes-Valera et al 2013) and pigs (Jutzeler et al 2018).…”
Section: Introductionmentioning
confidence: 99%